Pengaruh Tingkat Pengangguran Terbuka (TPT) dan Tingkat Kemiskinan Terhadap Pertumbuhan Ekonomi Di Provinsi Lampung - Shelisa, Indira Innaya; Setyanto, Alief Rakhman (Jurnal Ekonomika : INDEPENDEN, 2023)
Economic growth is a long-term problem that must be addressed by every country where it is expected that rapid economic growth will occur. The purpose of this research is to find out how the effect of the open unemployment rate, and the level of poverty on economic growth in Lampung province for the 2018-2022 period. This study uses a quantitative approach. The data used is secondary data originating from the Central Bureau of Statistics (BPS). The data analysis technique in this study used the time series method with the SPSS version 24.0 application. The data techniques used in this study are the classical assumption test, hypothesis testing, and linear regression analysis. The research results obtained show that the unemployment rate has a positive and significant effect on Economic Growth in Lampung Province for the 2018-2022 period, the poverty rate has a positive and significant effect on Economic Growth in Lampung Province for the 2018-2022 period